The Role of Catechin Compound and Its Derivates to Mitigate Methane Gas Production in the Rumen Fermentation - Mozart Nuzul Aprilliza; Y N Anggraeny; E Wina (Indonesian Center for Animal Research and Development, 2021)
Enteric fermentation and its corresponding to methane emissions take place in many wild and domestic ruminant species, such as deer, buffalo, cattle, goats, sheep. Ruminant animals are different from other animals in that they have a rumen, a large fore-stomach with a complex microbial environment. A resulting of this process is methane (CH4), which has a global warming potential (25 times that of carbon dioxide (CO2)). Because the digestion process is not 100% efficient, some of the energy intake is lost in the form of methane. Recently, natural plant products, such as tea leaves which are often inexpensive and environmentally safe have been introduced in methane mitigation strategies. Tea leaves have potential for use as an additives in ruminant diets. The adding of catechin 10-40 g/Kg DM were able to declined methane emission 7.4–13.5%. Furthermore, catechin could decrease the methane production. Catechin decreased CH4 production both in vitro and in vivo. Catechin causes direct inhibition of methanogens as well as may act as hydrogen sinks during degradation by rumen microbes via cleavage of ring structures and reductive dehydroxylation reactions. The objective of this paper is to review existing knowledge related to discuss how catechins can act as methane-lowering agents from rumen fermentation on ruminants.